2004
DOI: 10.1002/jid.1081
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative approach to impact analysis of microfinance programmes in Bangladesh—what have we learned?

Abstract: Abstract:The quantitative impact assessment of microfinance programmes, like the programmes themselves, originated in Bangladesh. This essay reflects on the significance and usefulness for present day researchers of the analytical advances made in Bangladesh since the beginning of the 1990s. Particularly in the area of selection bias, fungibility and the assessment of wider impacts, it argues, those advances are crucial, and need to be borne in mind by all practitioners; but financial sustainability remains an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 10 publications
2
48
0
Order By: Relevance
“…These findings are consistent with prior research, suggesting that household incomes play a significant role in the performance and growth of women owned micro and small businesses (Allen et al, 2006). Specifically, studies on micro-credit impact assessment have indicated that the growth of women owned enterprises supported by micro credit depends on household conditions (income) and other household endowments (Khalily, 2004). Our results have also established that while household income is positively correlated with enterprise profitability (r = 0.450, p <.01), it is negatively correlated with loan size (r = -0.290, p <0.01) (Table 3).…”
Section: Discussionsupporting
confidence: 67%
“…These findings are consistent with prior research, suggesting that household incomes play a significant role in the performance and growth of women owned micro and small businesses (Allen et al, 2006). Specifically, studies on micro-credit impact assessment have indicated that the growth of women owned enterprises supported by micro credit depends on household conditions (income) and other household endowments (Khalily, 2004). Our results have also established that while household income is positively correlated with enterprise profitability (r = 0.450, p <.01), it is negatively correlated with loan size (r = -0.290, p <0.01) (Table 3).…”
Section: Discussionsupporting
confidence: 67%
“…In cases in Malaysia, Bolivia, and Bangladesh, microfinance was found to be an effective tool for increasing income, assets, and spending Chana and Mazanah 2011;Mosley 2001). Another study by Khalily (2004) in Bangladesh found positive impacts to poverty, income change, consumption expenditures, net worth, asset accumulation, and education. Mawa (2008) further noted that while some problems existed, microfinance was able to make meaningful contributions to poverty alleviation, and concluded that institutions need to look more seriously at the diversified needs of the poor and target the extremely poor.…”
Section: Assessing the Role Of Microfinance On Poverty Alleviationmentioning
confidence: 98%
“…There is a wider acceptability of the notion that assess to microcredit by women in Bangladesh can bring about change in their socioeconomic situation (Khalily, 2004). After the introduction of micro credit, the women borrowers in Bangladesh got the chance to be income earning members of their families and this gave them higher authority with regards to purchasing power (Kohinur, 2007).…”
Section: Change In Purchasing Capacitymentioning
confidence: 99%